Delayed diagnosis of blunt thoracic aortic injury due to thoracic vertebral fracture: A case report and literature review - Lei, Xinhuan; Hong, Zhenghua; Pan, Weixing; Xiang, Jie; Luo, Hua (Frontiers in Surgery, 2022)
Blunt vascular injury of the aorta combined with thoracolumbar fracture is rare. Delayed diagnosis may have a catastrophic outcome. We present a case of blunt thoracic aortic injury combined with a vertebral body fracture at T10 after a fall from height in which the diagnosis was delayed. After consultation with the vascular and spinal surgeons, we performed a thoracic endovascular aortic repair. When the patient’s condition had stabilized, the fractures were reduced using posterior vertebral instrumentation. Prolonged compression of the thoracic aorta resulted in extensive necrosis of muscle tissues in the right lower leg. Fortunately, clinical and radiological examinations performed 7 months later did not reveal any further damage. Cases of thoracic vertebral fracture with concomitant blunt thoracic aortic injury reported in the literature are reviewed. Thoracic endovascular aortic repair is a feasible, safe, and effective minimally invasive treatment for aortic injury when combined with thoracic vertebral fracture.